(untitled) - Drifte, Reinhard (New York, 1990)
This book consists of the following 8 chapters: analyse the historical and institutional basic of Japan's international relations, Japan;s reactions to recent changes in the international environment through the introduction of the conceptual framework of the comprehensive security which was developed against a less benevolent strategic background, the expansion of Japan's economy, as well as the restructuring of its domestic base and the consequent repercussions on the direction of the country's foreign policy.